2019
DOI: 10.1016/j.pedneo.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal intrapartum antibiotics on the initial oral microbiome of neonates

Abstract: Neonatal oral microbiome; Maternal intrapartum antibiotics; 16S rRNA sequencing Objectives: Prior studies have proposed that maternal intrapartum antibiotic exposure shapes the gut microbiota and, subsequently the child's health. However, the effect of maternal intrapartum antibiotic exposure and its influence on the development of the neonatal oral microbiota in early infancy has not yet been reported. The aim of this study was to compare the initial oral microbiota immediately after birth of healthy infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…At 3 months, they show underrepresentation of Bacteroides, Parabacteroides, and higher Enterococcus and Clostridium (Azad et al, 2016), as well as a higher abundance of Enterobacteriaceae (Mazzola et al, 2016), as compared to nonantibiotic exposed infants. Similar results were reported in a recent study including 22 newborns which demonstrated that maternal intrapartum antibiotics can affect the infant oral microbiota with phyla Actinobacteria, Bacteroidetes, and Proteobacteria being more abundant in infants of antibiotic-treated mothers (Li et al, 2019). Another study in 28 preterm infants (with fecal samples collected on Day 7 and 14 from birth) demonstrated similar results with decreases in Bacteroidetes and…”
Section: Impact Of Antibiotics During Pregnancy and Lactationsupporting
confidence: 87%
“…At 3 months, they show underrepresentation of Bacteroides, Parabacteroides, and higher Enterococcus and Clostridium (Azad et al, 2016), as well as a higher abundance of Enterobacteriaceae (Mazzola et al, 2016), as compared to nonantibiotic exposed infants. Similar results were reported in a recent study including 22 newborns which demonstrated that maternal intrapartum antibiotics can affect the infant oral microbiota with phyla Actinobacteria, Bacteroidetes, and Proteobacteria being more abundant in infants of antibiotic-treated mothers (Li et al, 2019). Another study in 28 preterm infants (with fecal samples collected on Day 7 and 14 from birth) demonstrated similar results with decreases in Bacteroidetes and…”
Section: Impact Of Antibiotics During Pregnancy and Lactationsupporting
confidence: 87%
“…The use of amoxicillin has also been shown to reduce the abundances of Neisseria, Streptococcus, and Veillonella in the oral microbiota (Larsson Wexell et al, 2016;Moraes et al, 2020). In another study, a group of neonates was enriched in lipopolysaccharide biosynthesis and amino-acid-related metabolic functions after maternal antibiotic exposure, whereas the group of unexposed neonates was enriched in carbohydrate metabolic pathways (Li H. et al, 2019).…”
Section: Antibiotic Utilizationmentioning
confidence: 99%
“…All samples were collected by trained nurses according to the previously described protocol (18). During the sample collection process, nurses wore facial masks and sterile gloves and mothers did not handle to avoid possible contaminations.…”
Section: Subjects and Samplesmentioning
confidence: 99%
“…In this light, there were growing interests in understanding which endogenous and environmental factors influence the composition of the neonatal oral microbiome. More and more studies demonstrated that numerous factors were related to the initial colonization of the first oral microbiome (17,18), especially the status of mother, which was the primary source (19).…”
Section: Introductionmentioning
confidence: 99%